2000
DOI: 10.1016/s0735-1097(00)00775-0
|View full text |Cite
|
Sign up to set email alerts
|

Low apolipoprotein A-IV plasma concentrations in men with coronary artery disease

Abstract: The results of this cross-sectional study demonstrate for the first time an association between low apoA-IV concentrations and CAD in humans and suggest that apoA-IV may play an antiatherogenic role in humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
49
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 102 publications
(58 citation statements)
references
References 32 publications
8
49
1
Order By: Relevance
“…In line with these in vitro data, overexpression of ApoA-IV in transgenic mice led to reduced aortic lesions and protection against atherosclerosis [22,23]. These results were recently confirmed by case-control studies in three independent human populations: ApoA-IV plasma concentrations were found to be significantly lower in patients with coronary artery disease as compared to control groups [24,25]; a correlation between plasma ApoA-IV concentrations and atherosclerosis was also observed in patients with kidney failure [26].…”
Section: By the International Society Of Nephrologysupporting
confidence: 66%
See 1 more Smart Citation
“…In line with these in vitro data, overexpression of ApoA-IV in transgenic mice led to reduced aortic lesions and protection against atherosclerosis [22,23]. These results were recently confirmed by case-control studies in three independent human populations: ApoA-IV plasma concentrations were found to be significantly lower in patients with coronary artery disease as compared to control groups [24,25]; a correlation between plasma ApoA-IV concentrations and atherosclerosis was also observed in patients with kidney failure [26].…”
Section: By the International Society Of Nephrologysupporting
confidence: 66%
“…The usually observed mean ApoA-IV level in the general population measured with our assay is substantially higher (13 to 15 mg/dL) [24,30].…”
Section: Discussionmentioning
confidence: 85%
“…Apo A-IV is mainly related to cholesterol homeostasis and oxidative protection, and has been associated with the cardioprotective properties of the HDL particle [38]. Although Apo C-III protein is present in HDL, it is also a major protein in VLDL.…”
Section: Discussionmentioning
confidence: 99%
“…ApoAIV and adiponectin show anti-atherogenic and antioxidative properties and are negatively correlated with cardiovascular disorders1617. Adiponectin probably protects against cardiac remodeling by attenuating myocardial hypertrophy18; furthermore, it also has protective effects against different vascular disorders, such as endothelial dysfunction and hypertension, and inhibits platelet aggregation and inflammation (reviewed by ref.…”
Section: Discussionmentioning
confidence: 99%